Effect of medroxy-progesterone acetate on follicular growth and endometrial cycloxygenase-2 (COX-2) expression during the bovine estrous cycle - Portela,Valério M. (2010)
The objective of this study was to evaluate the effect of medroxy-progesterone acetate (MAP) with or without estradiol benzoate (EB) on follicular growth during the estrous cycle in cattle. In the first experiment, Hereford cows were synchronized with a synthetic analogue of PGF2 alpha and were treated with two different doses of MAP (250 or 500 mg) with or without EB for 7 days starting on day 8 of the estrous cycle. Follicular growth was inhibited (P<0.05) in all cows except controls and those receiving 250mg MAP without EB. Seventy-five percent of the animals (15/20) showed estrus on days 21 and 22 of the cycle rather than at MAP withdrawal, demonstrating that these treatments did not induce estrus. To determine whether the EB treatment altered endometrial sensitivity to oxytocin and thus the luteolytic cascade, multiparous pre-synchronized cows received 5 mg of EB followed 6 hours later with 50 IU of oxytocin (OT; n=9). Eight hours after EB injection, endometrial fragments were collected from the cows on days 4, 13 and 17 of the estrous cycle and COX-2 gene expression was measured by PCR. EB increased COX-2 mRNA levels only on day 17 of the estrous cycle (P<0.05). In conclusion, MAP alone or associated with EB is able to suppress bovine follicular growth. However, EB in the presence of MAP is not efficient to induce luteolysis in cows when injected on day 8 of the estrous cycle.